2018
DOI: 10.1007/s10278-018-0132-5
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Data Presentation on Physician Performance Utilizing Artificial Intelligence-Based Computer-Aided Diagnosis and Decision Support Systems

Abstract: Ultrasound (US) is a valuable imaging modality used to detect primary breast malignancy. However, radiologists have a limited ability to distinguish between benign and malignant lesions on US, leading to false-positive and false-negative results, which limit the positive predictive value of lesions sent for biopsy (PPV3) and specificity. A recent study demonstrated that incorporating an AI-based decision support (DS) system into US image analysis could help improve US diagnostic performance. While the DS syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 15 publications
3
33
0
1
Order By: Relevance
“…As technology evolves, its impact on the medical field increases. For example, artificial intelligence (AI) algorithms will shift the roles of physicians from a knowledgebased role into more of a skills-based role [42]. All of that information will be available in an AI-driven database that can not only bring up the information at a moment's notice, but also help to diagnoses.…”
Section: Discussionmentioning
confidence: 99%
“…As technology evolves, its impact on the medical field increases. For example, artificial intelligence (AI) algorithms will shift the roles of physicians from a knowledgebased role into more of a skills-based role [42]. All of that information will be available in an AI-driven database that can not only bring up the information at a moment's notice, but also help to diagnoses.…”
Section: Discussionmentioning
confidence: 99%
“…Thirty-seven publications were eventually included in this review. 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 Figure 1 presents the PRISMA flowchart.…”
Section: Resultsmentioning
confidence: 99%
“…Three studies reported on more than 1 CDSS (or using the same CDSS in different modalities). 21 , 31 , 42 A total of 107 main results were reported with statistical significance, and 41 were reported without it. Most studies defined statistical significance at P < .05, with some applying correction for multiple comparisons.…”
Section: Resultsmentioning
confidence: 99%
“…Diese Features wurden mittels supervidiertem Lernen erstellt. Im Gegensatz zu älteren rigiden CAD-Systemen aus der Mammographie wird diese Software durch fortwährendes Einspielen neuer Bilder mit assoziierter pathologischer Korrelation dynamisch korrigiert und weiterentwickelt, was jedoch neue Herausforderungen an die Qualitätskontrolle stellt [3].…”
Section: Künstliche Intelligenz In Der Brustsonographieunclassified